Evaluasi Karkas dan Rumah Potong Ayam Lokal di Beberapa Kabupaten di Daerah Istimewa Yogyakarta dan Jawa Tengah - Wahyu Supartono; Sri Raharjo; Sofyan Iskandar (agriTECH, 2003)
Local chickens are one of national assets which need serious consideration, because they have some advantages than imported ones. These local chicken are still used as raw material for some traditional foods or ceremonies. But the quality of their carcasses was still low, so that it was needed to observe them in the practices (at the slaughtering houses and the market). The observations were conducted in some regions; Surakarta and Sukoharjo (Middle Java), Yogyakarta city, Sleman and Bantu! (Yogyakarta Special Province). This research was focussed on chemical, physical and microbiological determination on local chicken carcasses, which were sold in the market and evaluastion on slaughtering houses in the five research locations. The results depicted, the local chicken carcasess had higher protein and calorie content, lower fat content than imported ones. Based on sensory evaluation, these chicken carcasses showed good physical appearance. The results on texture and colour test depicted, there were no significant differences among the. But the microbiological test poniled out, that all samples were containinted by Escherichia coil, Staphylococcus sp and Salmonella sp. The field observation on the slaughtering houses showed, that all houses did not implement the principles of equipment lay-out, processing flow, good sanitation and waste handling and hygienic material handling.